Determinants of Corporate Reputation towards Knowledge Sharing - NEMIÑO, ROMEL C (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
This paper examines the underlying relationship between corporate reputation and knowledge sharing of commercial bank employees in Caraga Region, Philippines. Its objective is to determine the levels of corporate reputation and knowledge sharing. In the same vein, correlation measures using the Pearson Product Moment Correlation between corporate reputation on knowledge sharing is also explored. Using the stratified random sampling technique, 400 bank employees across the region are identified as the primary respondents of this empirical research. As perceived by the respondents, findings reveal a very high level of corporate reputation and knowledge sharing among the bank employees. Moreover, strong evidence on the positive relationship between the constructs corporate reputation and knowledge sharing is uncovered. Among the dimensions of corporate reputation, corporate communication revealed the highest r-value when correlated with knowledge sharing. The findings of this study substantiate an empirical contribution not only to the banking industries but to other business organizations making this proposed research model as the laying ground for future policy reviews and formulations to improve business performance.